Neuromuscular profile of top-level youth taekwondo competitors assessed through tensiomyography - Croatian National Youth Taekwondo Team example - Sladic, N.; Cular, D.; Babic, M.; Kezic, A.; Tomase, T.; Zubac, D. (Acta Kinesiologica, 2025)
Purpose: This study aimed to investigate the neuromuscular profile of elite youth Taekwondo (TKD) athletes using tensiomyography (TMG) to assess lower-limb muscle contractile properties and estimate muscle fiber composition.